PRO-KONTRA ATAS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 46/PUU-VIII/2010 TENTANG KEDUDUKAN DAN HAK ANAK LUAR KAWIN - Lutfiyah, Novi (Mabahits : Jurnal Hukum Keluarga Islam, 2022)
This research uses qualitative methods, while the type of research is library research which is contextual interpretation by explaining: (1) What is the position and rights of children out of wedlock after the decision of the constitutional court number 46/PUU-VIII/2010 (2) What are the arguments of the pro and contra groups of people over the decision of the constitutional court number 46/PUU-VIII/2010. This study concluded that (1) illegitimate children can get the position and rights that exist in themselves, such as civil relations, maintenance rights, subsistence rights, and educational financing rights from their biological fathers as long as they can be proven based on science and technology or other tools. Other evidence as for the inheritance of the father, the child can only get it in the form of a will or a grant. (2) The arguments of the pro group are more in terms of the interests of the child in giving an opinion where the child should be given legal protection against acts of discrimination or things that threaten the safety of the child and confirms guarantess of constitutional rights such as the right to life and rights private. Meanwhile the opposing group gave an argument that looked more from a religious perspective on the validity of their parents marriage, because how could a child resulting from a relationship outside of marriage have the same position and rights as a legitimate child so that it would have a bad impact and facilitate moral depravity, prostitution and the existence of a decision. This is considered to have violated Islamic theachings and even changed the order of life of Muslims which had been in effect and made it difficult for inheritance to be distributed. Key Word: Pros-Cons, The Position and Rights of Children Out of Wedlock, Constitutional Court Decision.